Atypical location of double-strand origin of replication (nic site) on the plasmid pGA1 from Corynebacterium glutamicum - Abrhámová, Z; Pátek, M; Nesvera, J (Folia microbiologica, 2002)
The double-strand origin of replication (dso) of the rolling-circle-replicating (RC) plasmid pGA1 from Corynebacterium glutamicum was analyzed using the runoff DNA synthesis assay. The site- and strand-specific breakage of double-stranded plasmid DNA, representing the nic site of dso, was localized precisely within the sequence 5'-CTGG decreases AT-3' in the distal part of the pGA1 rep gene. This location of dso differs from the dso positions found on other RC plasmids and is in agreement with the classification of the plasmid pGA1 into a new group of RC plasmids.
Keywords: replikační počátek; plazmidy; Replication Origin; Corynebacterium; sekvence nukleotidů; Plasmids; Base Sequence; Chromosome Mapping; DNA, Bacterial; DNA bakterií; mapování chromozomů